2020
DOI: 10.29136/mediterranean.691432
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’den toplanan yerel soğan çeşitlerinin soğan sak nematodu Ditylenchus dipsaci’ye dayanıklılık reaksiyonları

Abstract: A total of 27 accessions of different onion landraces from Turkey were screened for their resistance to stem and bulb nematode. The study was carried out in a growth chamber at 20°C, with a 16/8 h (light/dark) photoperiod and at 70% relative humidity. The plants were grown in 7 X 8 cm diameter plastic pots filled with a mixture of 45% sand, 45% clay loam soil, 10% organic matter. Two hundred nematodes in 10 µl nematode suspension were inoculated to each plant at the 3-4 leaves stage. Plants were harvested six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similar results were revealed in a study by Yavuzaslanoğlu (2019), where significant differences were detected in some genotypes for plant length and plant diameter, but no significant differences were found in plant weight. Some varieties of oat, rye, bean, clover and onion have been reported to be resistant to races of stem and bulb nematode (Plowright et al, 2002;Yavuzaslanoğlu, 2019;Yavuzaslanoğlu & Ozsoy, 2020). However, to our knowledge, there are no studies conducted to determine the resistance of garlic plant varieties to stem and bulb nematode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were revealed in a study by Yavuzaslanoğlu (2019), where significant differences were detected in some genotypes for plant length and plant diameter, but no significant differences were found in plant weight. Some varieties of oat, rye, bean, clover and onion have been reported to be resistant to races of stem and bulb nematode (Plowright et al, 2002;Yavuzaslanoğlu, 2019;Yavuzaslanoğlu & Ozsoy, 2020). However, to our knowledge, there are no studies conducted to determine the resistance of garlic plant varieties to stem and bulb nematode.…”
Section: Discussionmentioning
confidence: 99%
“…So far, some varieties of clover, rye, bean, oat and onion that show resistance to different races of the stem and bulb nematode have been identified (Plowright et al, 2002;Yavuzaslanoğlu, 2019;Yavuzaslanoğlu & Ozsoy, 2020). However, no study has been reported about resistance in garlic to stem and bulb nematode.…”
Section: Introductionmentioning
confidence: 99%